Foregrounding In Expressing Melancholy And Nostalgia In Lana Del Rey’s Song Lyrics - Yohana Insani Saragih; Tiara K Pasaribu; Rotua Elfrida (Jurnal Ilmiah Mandala Education (JIME), 2026)
This study discusses foregrounding in expressing melancholy and nostalgia in Lana Del Rey’s song lyrics. Although many studies have analyzed figurative language in song lyrics, few have focused on foregrounding as the main analytical framework. This study aims to identify the forms and functions of foregrounding in the songs The Greatest and Happiness Is a Butterfly. This research applies a descriptive qualitative method based on Geoffrey Leech’s (1969) theory of foregrounding. The findings show that foregrounding is realized through semantic deviation and parallelism. Semantic deviation appears through figurative expressions and is more dominant, functioning to construct melancholy, while parallelism appears through repetition and functions to construct nostalgia. In conclusion, this study shows that foregrounding plays an important role in expressing emotional meanings in song lyrics through non-literal and patterned language. This study contributes to stylistic analysis by explaining how linguistic features construct emotional meaning in contemporary song lyrics.